Analysis of International Aspects on the Balance of Supply and Demand in the Domestic Market - Fidatiara Anggraini; Riani, Lilia Pasca (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This study aims to analyze the impact of international factors on the balance of supply and demand in the Indonesian domestic market. The main focus of this study is changes in trade policy, fluctuations in the rupiah exchange rate, and global price dynamics in influencing the domestic market. In addition, the study identifies adaptation strategies that can be implemented by governments and the private sector to address global economic challenges. Design/Method/Approach: This study uses a qualitative approach with a literature study method. Various data sources such as scientific journals, policy reports, and data from official institutions such as Bank Indonesia and the WTO were analyzed using a thematic synthesis approach to identify patterns and relationships between international factors and the balance of supply and demand in Indonesia. Research Finding: The analysis shows that international factors such as fluctuations in global commodity prices, trade partner policies, the rupiah exchange rate, the global economic crisis, and geopolitical stability have a significant impact on the balance of supply and demand in the domestic market. Adaptation strategies such as diversifying export markets, increasing the competitiveness of local products, and responsive monetary and fiscal policies can help Indonesia face global economic challenges. Theoretical contribution/Originality: This research offers a new perspective by integrating international factors in a comprehensive analysis of the balance of supply and demand in Indonesia. By highlighting the linkages between global monetary policy, the structure of international supply chains, and the response of domestic markets to external shocks, this study enriches the economic literature in the context of an open economy. Practitionel/Policy implication: The results of this research can be used by policymakers to design economic regulations that are more adaptive to global dynamics. For the private sector, the insights from this research can be fundamental in business decision-making strategies, especially in the face of global market fluctuations. Research limitation: This study is limited to a literature-based analysis, so it does not include more specific empirical data. Further studies with quantitative approaches or econometric models are needed to measure the direct impact of international factors on the balance of supply and demand in Indonesia.